2020
DOI: 10.1080/15476286.2019.1709747
|View full text |Cite
|
Sign up to set email alerts
|

Essential functions of the CNOT7/8 catalytic subunits of the CCR4-NOT complex in mRNA regulation and cell viability

Abstract: Shortening of mRNA poly(A) tails (deadenylation) to trigger their decay is mediated mainly by the CCR4-NOT deadenylase complex. While four catalytic subunits (CNOT6, 6L 7, and 8) have been identified in the mammalian CCR4-NOT complex, their individual biological roles are not fully understood. In this study, we addressed the contribution of CNOT7/8 to viability of primary mouse embryonic fibroblasts (MEFs). We found that MEFs lacking CNOT7/8 expression [Cnot7/8-double knockout (dKO) MEFs] undergo cell death, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…Liver-specific disruption of Cnot1 causes lethal hepatitis associated with elongated mRNA poly(A) tails Suppression of CNOT1 largely abrogated deadenylase activity (Temme et al, 2010;Ito et al, 2011;Nousch et al, 2013;Mostafa et al, 2020), suggesting that CNOT1 is an essential scaffold subunit in the CCR4-NOT complex in vivo. We generated conditional KO mice for Cnot1 (Cnot1 fl/fl mice) by inserting loxP sequences into the Cnot1 gene locus so that exons 20 and 21 were deleted (Fig S1A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver-specific disruption of Cnot1 causes lethal hepatitis associated with elongated mRNA poly(A) tails Suppression of CNOT1 largely abrogated deadenylase activity (Temme et al, 2010;Ito et al, 2011;Nousch et al, 2013;Mostafa et al, 2020), suggesting that CNOT1 is an essential scaffold subunit in the CCR4-NOT complex in vivo. We generated conditional KO mice for Cnot1 (Cnot1 fl/fl mice) by inserting loxP sequences into the Cnot1 gene locus so that exons 20 and 21 were deleted (Fig S1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we provide evidence that the CCR4-NOT deadenylase complex plays critical roles in liver homeostasis. Liver-specific disruption of Cnot1, which encodes a scaffold subunit of the complex, resulted in substantial elongation of bulk RNA poly(A) tails, as in the case of Drosophila S2 cells, Caenorhabditis elegans, and MEFs (Temme et al, 2010;Nousch et al, 2013;Mostafa et al, 2020), further indicating an essential role of CNOT1 in CCR4-NOT complex-mediated mRNA deadenylation in vivo. Consistent with previous reports that poly(A) tails stabilize mRNAs in eukaryotes (Dreyfus & Regnier, 2002;Weill et al, 2012), more than 80% of the mRNAs that we analyzed showed elongated half-lives in livers from Cnot1-LKO mice (Fig 7A).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, microarray analysis showed that CNOT7 and CNOT8, despite high homology, have specific substrates for their enzymatic activity (10,17). Some other studies have suggested, combined depletion of CNOT7 and CNOT8 subunits cause mRNA decay in human HTGM5 cells, reduce cell proliferation in MCF7 breast cancer cells and result in cell viability reduction and cell death in mouse embryonic fibroblasts (MEFs) (11,22,23). Accordingly, it has been suggested that alterations of CNOT7 and CNOT8 expression are relevant to the development and progression of cancer (17,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CNOT7 null mice show defects in spermatogenesis, even in the presence of CNOT8, suggesting that CNOT7 and CNOT8 may not be entirely redundant in function [60,61]. In mammalian cells, the complex contains either CNOT7 or CNOT8, suggesting they compete for binding to CNOT1 [18,19].…”
Section: Mrna Turnover and Deadenylationmentioning
confidence: 99%
“…These appear to form various heterodimers, CNOT7/CNOT6, CNOT7/CNOT6L, CNOT8/CNOT6, and CNOT8/CNOT6L. Thus, the complex contains either CNOT7 or CNOT8, suggesting they compete for binding to CNOT1 [18,19]. While the E3 ubiquitin ligase Not4 is consistently present in the yeast complex, CNOT4 is not as stably associated as the other subunits in mammalian cells [18].…”
Section: Introductionmentioning
confidence: 99%